Innovation and Informality: An Analysis With the Colombian Manufacturing Industry 2007 to 2016 - Fernando Barrios Aguirre; Sandra Yaneth Mora Malagón; Luis Carlos Castillo Téllez (SAGE Open, 2023)
The purpose of the research is to analyze the effects caused by the competition of companies with labor informality on the innovative behavior of companies with labor formality that compete in the same industry. This research references and analyzes the implementation of law 1429 of 2010, which stimulates the formalization of labor and informal firms. The results estimated by fixed effects exhibit a positive and significant effect of the competition of companies with labor informality in the total innovation of formal companies. On the other hand, once the formalization and job creation policy was implemented, there was a decrease in total innovations of formal companies. The empirical analysis also highlights a different impact of informal competition depending on whether the innovation is in process or product. In particular, this research finds that process innovations are more intensely affected by labor informality than product innovations. The quantitative strategy relies on a panel data econometric model between 2007 and 2016 using the Survey of Innovation and Technological Development (EDIT) and the Great Integrated Household Survey (GEIH) provided by the National Administrative Department of Statistics (DANE).